Geotechnical Characteristics of Tanjung Bin Coal Bottom Ash - Abuelgasim, R; Rashid, A S A; Bouassida, M; Shien, N; Abdullah, M H (IOP conference series. Materials Science and Engineering, 2020)
Coal is considered one of the major sources of power-generation in Malaysia. The Coal-fired power plant is a kind of power plant that uses coal to generate electricity. The globally increasing demand for energy has led to an increase in the number of installation of coal-fired power plants. With the growth in coal-burning power plants, massive amounts of coal bottom ash have been produced as waste material. This article presents an experimental study on the geotechnical characteristics of Tanjung bin coal bottom ash and compares them with the properties of the natural granular soil focusing on the physical and mechanical characteristics namely; grain size distribution, specific gravity, compaction, permeability, shear strength, and relative density. Results revealed that the Tanjung bin bottom ash has geotechnical properties similar to the natural granular material, therefore it can be utilized as a substitute material to sand in several geotechnical application.